Celowość tworzenia zintegrowanego systemu zarządzania pracownikami wiedzy - Morawski, Mieczysław (The Advisability of Creating the Integrated System of Management of Workers of Knowledge, 2006)
Introduction of the management of knowledge in an enterprise requires managers' maturity. Experience in using other modern conceptions of management points to the necessity of applying system solutions. Particularly essential is creation of the workers of knowledge management system. It is indispensable as the meaning of low knowledge steadily increases.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 165-173